Poster: We Are Well: Wayapa movement ... - Burke, Geraldine; Pettengell, Priscilla; Hanger, Chris (Monash University, 2023)
The poster, 'We Are Well: Wayapa movement ’ is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. It showcases Aunty Karan leading Wayapa movement with children, Monash students, older community members, teachers and researchers. Poster text: Thanks, Aunty Karan. I love moving with the grass under my bare feet and feeling like wind, like lightning, like the eels, and more. I feel so special and connected to the land. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Megan Adams, Aislinn Lalor, Chris Hange r Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists: Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara and ...